Mechanical And Thermal Performance Of Lightweight Geopolymers Foamed Using Aluminium Powder - Mohamed Aliff Izham Mohamed Zakhari (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
The scope of this research is basically to study the physical, mechanical and characteristic of the thermal performance of lightweight geopolymer by the addition of aluminium powder. The performance of pure geopolymer is compared to the performance of geopolymer with the addition of aluminium powder with the same parameter by varying Al powder content and elevated temperature exposure as thermal performance profile.